2021
DOI: 10.1016/j.jcot.2020.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Indeterminate pulmonary nodules are not associated with worse overall survival in Ewing Sarcoma

Abstract: Aim: Lung metastases are a negative prognostic factor in Ewing sarcoma, however, the incidence and significance of sub-centimetre pulmonary nodules at diagnosis is unclear. The aims of this study were to (1): determine the incidence of indeterminate pulmonary nodules (IPNs) in patients diagnosed with Ewing sarcoma (2); establish the impact of IPNs on overall and metastasis-free survival and (3) identify patient, oncological and radiological factors that correlate with poorer prognosis in patients that present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Previous studies in other types of sarcoma have produced various results; Tsoi et al demonstrated worse OS in patients with IPNs in osteosarcoma [ 13 ], whilst Ghosh et al found no difference [ 14 ]. Tsoi et al also studied the relevance of IPNs in Ewing sarcoma, finding no difference in OS [ 15 ]. It is important to note that Tsoi et al’s sample size for their osteosarcoma study was significantly larger than the other two studies mentioned, allowing for much greater power to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies in other types of sarcoma have produced various results; Tsoi et al demonstrated worse OS in patients with IPNs in osteosarcoma [ 13 ], whilst Ghosh et al found no difference [ 14 ]. Tsoi et al also studied the relevance of IPNs in Ewing sarcoma, finding no difference in OS [ 15 ]. It is important to note that Tsoi et al’s sample size for their osteosarcoma study was significantly larger than the other two studies mentioned, allowing for much greater power to detect a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Metastatic disease is a common cause of death in patients with bone sarcoma [ 1 ]. Synchronous metastases are present in 15–20% of osteosarcomas [ 2 , 3 , 4 ] and up to 25% of Ewing sarcomas [ 5 , 6 , 7 ], while 20–50% of osteosarcoma and Ewing sarcoma patients will develop secondary metastases, most commonly affecting the lungs [ 8 , 9 , 10 ]. Apart from chemotherapy (CTX) and radiotherapy (RTX), resection of metastases in general, and lung metastases in particular, has become an important therapeutic option in bone sarcoma patients [ 11 , 12 ], in addition to other local treatment options [ 13 ].…”
Section: Introductionmentioning
confidence: 99%